Fenomena Komunikasi melalui Media Sosial di Kalangan Remaja - Ainiyah, Nur (Jurnal Askopis, 2017)
This research is oriented to communicating through social media among adolescent Wonorejo. With the focus of research on how social media phenomenon in interpretation among adolescents? And how the phenomenon of communication through social media woke up among teenagers? So the theoretical foundations relevant to this research are phenomenology, social media concept and concept of interpersonal communication. Data analysis used in this research is communication phenomenology analysis that is by analyzing every phenomenon of interpersonal communication done by adolescent through social media. By using interview technique, observation and documentation technique in collecting data, it is found that Wonorejo teenagers have verbal and nonverbal communication content by utilizing social media through Facebook account, Whatsapp even group communication room through online game creating cyberculture among teenagers.Â Penelitian ini berorientasi pada komunikasil melalui media social di kalangan remaja Wonorejo. Dengan fokus penelitian bagaimana fenomena media social di interpretasi di kalangan remaja? Dan bagaimana fenomena komunikasi melalui media social terbangun di kalangan remaja? Maka landasan teoritis yang relevan dengan penelitian ini adalah fenomenologi, konsep media social dan konsep komunikasi interpersonal. Analisa data yang digunakan dalam penelitian ini adalah analisa fenomenologi komunikasi yakni dengan menganalisa setiap fenomena-fenomena komunikasi interpersonal yang dilakukan remaja melalui media social. Dengan menggunakan teknik wawancara, observasi dan teknik dokumentasi dalam pengumpulan data diperoleh hasil penelitian bahwa remaja Wonorejo memiliki konten komunikasi verbal dan nonverbal dengan memanfaat kan media sosial melalui akun Facebook, Whatsapp bahkan ruang komunikasi secara kelompok melalui game online menciptakan cyberculture di kalangan remaja.